TI_GERICHTE 11.2007.48 vom 2. Juli 2008 , Esercizio di un diritto di ricupera: iscrizione nel registro fondiario - TI Tribunale d'appello (2008)
Esercizio di un diritto di ricupera: iscrizione nel registro fondiario